Pengaruh Audit Internal Dan Good Corporate Governance Terhadap Nilai Perusahaan - Rahadian Amrullah; Indah Kristianti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effect of internal audit and good corporate governance on firm value in financial sector companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The study employed a quantitative approach with an associative research design. Secondary data were obtained from annual reports and financial statements of the sampled companies. The sample consisted of 24 financial sector companies selected using purposive sampling, resulting in 48 observations. Data were analyzed using panel data regression with the assistance of Eviews-12 software. The results indicate that internal audit, proxied by the number of internal auditors, has no significant effect on firm value, as evidenced by a probability value of 0.4394. Good corporate governance, proxied by institutional ownership, also has no significant effect on firm value, with a probability value of 0.7023. Simultaneous testing shows a Prob(F-statistic) value of 0.6532, indicating that internal audit and good corporate governance jointly have no significant effect on firm value. These findings suggest that internal monitoring mechanisms and corporate governance practices in the financial sector have not been sufficiently effective in influencing investor perceptions and enhancing firm value in the capital market